The Effectiveness of the Modeling Method in Learning Writing Poetry Skills - Efrianto (Journal of Positive School Psychology, 2023)
During short interviews concerning students' writing poetry skills, some phenomena were found. They are; 1) students find it difficult to find ideas when writing a poem; 2) difficult to express ideas and transfer them into a poem; 3) students are lack interest in writing poems because of the unsatisfactory teaching method. This study aimed to determine the effect of modeling methods on poetry writing skills based on image themes. The modeling methods based on images will serve as a medium for students when creating poetry. This study applied the experimental method with a treatment design of level 2 x 2. The research took place at the Faculty of Language and Arts, State University of Padang. The instrument used in this study was the student's work. Based on the result, it was found that there is a significant difference in students who were treated using the modeling method as an experimental group when compared to students who get treatment using the learning community method as a control class group. The average results score in the experimental group is 81.57 and 78.14 in the control class. The result shows that learning poetry writing skills using the modeling method effectively helps students learn writing skills